UPAYA MENINGKATKAN KOMPETENSI DOSEN - Muflihin, Muh. Hizbul (Forum Tarbiyah, 2011)
Abstract: Lecturers are professionals with a primary task of carryingout the learning process. If lecturers can create and maintainrelationships between each other, both with managers, their fellow,students, and staff, based on the work environment and in the overallrelationship, it will create a comfortable working environment. As aprofessional position, lecturers should improve the knowledge,attitudes, and skills continuously. In addition the lecturer should respondto the challenges of social development, the professorship shouldalways be developed. Efforts to improve the competence of lecturerscan be done by always trying to be able to analyze the main tasksassociated with courses (curriculum) to be designed into thepreparation of good teaching, seminars / workshops, conduct researchand use it for improving the quality of learning, and always read thenewly published books. Competence of lecturer is not a fixed price,therefore the quality of lecturers competencies will be re-tested atany time, to ensure that the lecturers are still worthy to teach andperform other tasks.